Color lures in orb-weaving spiders: a meta-analysis. (21st January 2020) - Ximenes, Nathalia G; Moraes, Vinicius De Souza; Ortega, Jean C G; Gawryszewski, Felipe M
Abstract: Lures are deceptive strategies that exploit sensory biases in prey, usually mimicking a prey's mate or food item. Several predators exploit plant–pollinator systems, where visual signals are an essential part of interspecific interactions. Many diurnal, and even nocturnal, orb-web spiders present conspicuous body coloration or bright color patches. These bright colors are regarded as color-based lures that exploit biases present in insect visual systems, possibly mimicking flower colors. The prey attraction hypothesis was proposed more than 20 years ago to explain orb-web spider coloration. Although most data gathered so far has corroborated the predictions of the prey attraction hypothesis, there are several studies that refute these predictions. We conducted a multilevel phylogenetic meta-analysis to assess the magnitude of the effect of conspicuous orb-web spider body coloration on prey attraction. We found a positive effect in favor of the prey attraction hypothesis; however, there was substantial heterogeneity between studies. Experimental designs comparing conspicuous spiders to painted spiders or empty webs did not explain between-studies heterogeneity. The lack of theoretical explanation behind the prey attraction hypothesis makes it challenging to address which components influence prey attraction. Future studies could evaluate whether color is part of a multicomponent signal and test alternative hypotheses for the evolution of spider colors, such as predator avoidance and thermoregulation. Lay Summary: Many orb-web spiders have conspicuous body coloration, which may lure insects, increasing spiders' foraging success. Flower coloration mimicry has been suggested as a possible explanation for this phenomenon. We reviewed and produced a synthesis of all studies on this topic via a meta-analysis. We have confirmed the prey attraction hypothesis, but we found significant heterogeneity among studies. The prey attraction hypothesis may not be the only explanation for the whole group of bright colored orb-web spiders.